Zinc and Copper Levels in Patients with Primary Hypertension and Normotension - Arinda Lironika Suryana; Bambang Wirjatmadi; Merryana Adriani (Makara Journal of Health Research, 2015)
One of the causes of primary hypertension is an exposure to free radicals. The formation of free radicals in the body can be prevented by taking antioxidants. Zinc and copper are cofactors of endogenous antioxidant enzyme superoxide dismutase. This study aimed to analyze the differences of zinc and copper levels in primary hypertensive and normotensive patients. This was an analytical observational study with cross sectional design and simple random sampling method. Subjects were patients aged 40-70 years at Haji General Hospital consisting of 15 primary hypertensive patients and 15 normotensive individuals (comparison group). Data was collected through interviews and laboratory test of blood samples. Zinc and Copper serum concentrations were measured by AAS. Data were analyzed by chi-square and independent samples t-test. The results showed that the mean levels of zinc and copper in primary hypertensive patients was lower than normotensive. However, statistically there was no difference in zinc serum levels (p=0.852) in the two groups, and there was a significant difference in copper serum levels (p=0.032). It can be concluded that there were differences in copper serum levels between the two groups but not with the levels of zinc.